Oxidative couplings on tryptophan-based diketopiperazines leading to fused and bridged chemotypes. Issue 18 (16th February 2017) - Mendive-Tapia, Lorena; Albornoz-Grados, Arantxa; Bertran, Alexandra; Albericio, Fernando; Lavilla, Rodolfo
Abstract : Selective C–C and C–N oxidative couplings on tryptophan-based diketopiperazines allow the direct access to two novel scaffolds. Abstract : New chemotypes are obtained from tryptophan-containing diketopiperazines through selective C–C or C–N intramolecular oxidative couplings. The choice of the oxidant source dictates the outcome of the reaction.